2011
DOI: 10.1016/j.limno.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Salt pollution of the middle and lower sections of the river Werra (Germany) and its impact on benthic macroinvertebrates

Abstract: a b s t r a c tIn two survey phases (2003 and 2008) organic, nutrient and salt contamination parameters have been investigated in the lower Werra in order to estimate the importance of these different kinds of pollution for the quality component of macroinvertebrates according to the European Water Framework Directive. The chemical and biological investigations have been carried out comparing a "reference" section without salt contamination with the salt contaminated section due to the potash mining industry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 8 publications
5
37
0
1
Order By: Relevance
“…These findings align with those of previous studies, which reported that biological quality of salt polluted streams can be affected by conductivities as low as 1.5 mS cm -1 (Dunlop et al, 2005;Hart et al, 1991;Horrigan et al, 2005;Kefford et al, 2011), or even lower (Cormier et al, 2013;Kefford et al, 2011). Anyhow, the damage to the aquatic invertebrate community can be expected to increase with increasing conductivity (Berezina, 2003;Böhme, 2011;Braukmann and Böhme, 2011;Cañedo-Argüelles et al, 2012;Hart et al, 1991;Horrigan et al, 2005;Pinder et al, 2005;Piscart, 2005;Williams et al, 1999). It is important to notice the reduction in EPT taxa at sites P3 and P4, and IMMi-L, Iberian Mediterranean Multimetric Index, using qualitative data (Munné and Prat, 2009); IMMi-T, Iberian Mediterranean Multimetric Index, using quantitative data (Munné and Prat, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings align with those of previous studies, which reported that biological quality of salt polluted streams can be affected by conductivities as low as 1.5 mS cm -1 (Dunlop et al, 2005;Hart et al, 1991;Horrigan et al, 2005;Kefford et al, 2011), or even lower (Cormier et al, 2013;Kefford et al, 2011). Anyhow, the damage to the aquatic invertebrate community can be expected to increase with increasing conductivity (Berezina, 2003;Böhme, 2011;Braukmann and Böhme, 2011;Cañedo-Argüelles et al, 2012;Hart et al, 1991;Horrigan et al, 2005;Pinder et al, 2005;Piscart, 2005;Williams et al, 1999). It is important to notice the reduction in EPT taxa at sites P3 and P4, and IMMi-L, Iberian Mediterranean Multimetric Index, using qualitative data (Munné and Prat, 2009); IMMi-T, Iberian Mediterranean Multimetric Index, using quantitative data (Munné and Prat, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Salt pollution also had clear effects on the aquatic macroinvertebrate communities, as had been previously reported for streams affected by potash mining in the Werra River basin (Bäthe and Coring, 2011;Braukmann and Böhme, 2011) and for the Llobregat River (Prat et al, 1983;Prat and Rieradevall, 2006). Taxa richness strongly responded to salinization, with only 7 taxa being registered in site P4 (conductivity=11.0 mS cm -1…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Beside an increased osmotic stress directly determining the viability of populations, stress induced responses of aquatic organisms include shifts in feeding type composition (Kefford et al, 2012), the impediment of growth (Roller and Stickle, 1985), as well as the impairment of different stages within the insect live cycle such as oviposition, pupation and emergence (Piscart et al, 2006). Moreover, salinization was found to enhance the establishment of exotic invasive species (Piscart et al, 2005b;Braukmann and Böhme, 2011), with brackish water species (i.e. osmoregulators) colonizing freshwater ecosystems.…”
Section: Introductionmentioning
confidence: 99%